Distress and coping mechanisms among people with diabetes: cross-sectional assessment from an NCD screening clinic of a tertiary care hospital in North India - Madhur Verma; Shivani Sidana; Prakash Kumar; Omna Singh; Vandana Esht; Karthick Balasubramanian; Nitin Kapoor; Rakesh Kakkar; Sanjay Kalra (Diabetology & Metabolic Syndrome)
Abstract Background Of the numerous complications encountered by people with diabetes (PWD), the effect on mental health is concerning. Within mental health, diabetes distress (DD) occurs when a patient has unfavourable emotional stress while managing their condition, which can be managed by coping strategies but are less studied together in Indian settings. So, the present study aimed to determine the proportion of DD and associated factors and coping skills among the PWD. Methods Cross-sectional study was conducted among 596 clinically stable, ambulatory PWD visiting the NCD clinic of a tertiary care centre in North India between June 2023 and January 2024 and recruited using a systematic random sampling technique. DD was the primary dependent variable assessed using the Hindi version of the Diabetes Distress Scale (DDS). Coping was assessed using a GlucoCoper scale. Independent variables included socio-demographic and clinic history variables. Bivariate analysis described the sample characteristics. Multivariable binary logistic regression analysis explored the factors affecting the DD. The study was ethically approved, and written informed consent was obtained from the patients. Results Of the 596 study participants, 17.4% depicted uncontrolled diabetes, while 18.1% PWD experienced moderate to severe DD, with emotional distress depicting the highest prevalence (23.8%). Significantly increased odds of living with DD in professionals compared to Clerical, shop-owners, farmers with less monthly average income (vs. the group with unstable income), tobacco users, and those with uncontrolled disease. Overall, scores for negative coping were higher than positive coping, with significant differences between the two types among the participants with DD. Conclusions The study underscores the complex interplay between diabetes control, distress, and coping mechanisms in patients attending an NCD screening clinic. The findings highlight the need for a holistic approach to diabetes management that addresses not only the physical aspects but also patients’ emotional and psychological well-being.